Investigations on the spectroscopic properties and laser performance of Tm3+/Ho3+-SrLaGa3O7 crystal. (April 2019) - Gao, Shufang; Xu, Shan; Tu, Chaoyang
Highlights: The first demonstrates spectroscopic and laser properties of Tm 3+ /Ho 3+ -SLGO Crystal. The stimulated emission cross-sections are larger than YAG and YAP. The maximum output powers of 6.15 W for a-cut crystal have been obtained. Abstract: The Tm 3+ /Ho 3+ -SrLaGa3 O7 crystal was grown using the Czochralski (CZ) method. The absorption spectra, the fluorescence spectra around 2.0 μm and energy-transfer (ET) schemes between Tm 3+ ions and Ho 3+ ions has been studied. The lasing performance of Tm 3+ /Ho 3+ -SrLaGa3 O7 crystal for a-cut and c-cut pumped by a fiber-coupled laser diode laser are presented in this paper. The maximum output powers of 6.15 W for a-cut crystal at 2041 nm and 2.51 W for c-cut crystal at 2044 nm have been obtained, respectively. The maximum slope efficiency in terms of absorbed pump power nearly reached 36.5% for the a-cut crystal and about 18.8% for the c-cut crystal. In addition, the width of tuning can reach about 450 nm, suggesting the potential of these crystals for ultrashort pulse generation by mode-locking.